2015
DOI: 10.3354/meps11336
|View full text |Cite
|
Sign up to set email alerts
|

Antarctic phytoplankton down-regulate their carbon-concentrating mechanisms under high CO2 with no change in growth rates

Abstract: High-latitude oceans, in particular the coastal Western Antarctic Peninsula (WAP) region of the Southern Ocean, are experiencing a rapidly changing environment due to rising surface ocean temperatures and CO 2 concentrations. However, the direct effect of increasing CO 2 on polar ocean primary production is unclear, with a number of experiments showing conflicting results. It has been hypothesized that increased CO 2 may cause a reduction of the energy-intensive carbon concentrating mechanism (CCM) in phytopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 65 publications
4
47
1
Order By: Relevance
“…Tolerance of CO 2 levels up to ∼ 1000 µatm has often been observed in natural phytoplankton communities in regions exposed to fluctuating CO 2 levels. In these communities, increasing CO 2 often had no effect on primary productivity (Tortell et al, 2000;Tortell and Morel, 2002;Tortell et al, 2008b;Hopkinson et al, 2010;Tanaka et al, 2013;Sommer et al, 2015;Young et al, 2015;Spilling et al, 2016) or growth (Tortell et al, 2008b;Schulz et al, 2013), although an increase in primary production has been observed in some instances (Riebesell, 2004;Tortell et al, 2008b;Egge et al, 2009;Tortell et al, 2010;Hoppe et al, 2013;Holding et al, 2015). These differing responses may be due to differences in community composition, nutrient supply, or ecological adaptations of the phytoplankton community in the region studied.…”
Section: Ocean Acidification Effects On Phytoplankton Productivitymentioning
confidence: 89%
See 3 more Smart Citations
“…Tolerance of CO 2 levels up to ∼ 1000 µatm has often been observed in natural phytoplankton communities in regions exposed to fluctuating CO 2 levels. In these communities, increasing CO 2 often had no effect on primary productivity (Tortell et al, 2000;Tortell and Morel, 2002;Tortell et al, 2008b;Hopkinson et al, 2010;Tanaka et al, 2013;Sommer et al, 2015;Young et al, 2015;Spilling et al, 2016) or growth (Tortell et al, 2008b;Schulz et al, 2013), although an increase in primary production has been observed in some instances (Riebesell, 2004;Tortell et al, 2008b;Egge et al, 2009;Tortell et al, 2010;Hoppe et al, 2013;Holding et al, 2015). These differing responses may be due to differences in community composition, nutrient supply, or ecological adaptations of the phytoplankton community in the region studied.…”
Section: Ocean Acidification Effects On Phytoplankton Productivitymentioning
confidence: 89%
“…This process requires additional cellular energy (Raven, 1991) and numerous studies have suggested that the energy savings from down-regulation of CCMs in phytoplankton could explain increases in rates of primary productivity at elevated CO 2 levels (e.g. Cassar et al, 2004;Tortell et al, 2008bTortell et al, , 2010Trimborn et al, 2013;Young et al, 2015). In Antarctic phytoplankton communities, Young et al (2015) showed that the energetic costs of CCMs are low and any down-regulation at increased CO 2 would provide little benefit.…”
Section: Ocean Acidification Effects On Phytoplankton Productivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Cells regulate their CCM to maintain an intracellular concentration of CO 2 that saturates Rubisco by ~80% 8,9 . Correspondingly, downregulation of the CCM in response to high CO 2 should have little effect on the intracellular CO 2 to O 2 ratio, resulting in no change in the rate of photorespiration.…”
Section: News and Viewsmentioning
confidence: 99%